Phase Equilibrium Study of the CaO–ZnO System. Issue 11 (29th July 2016) - Xia, Longgong; Liu, Zhihong; Taskinen, Pekka
Abstract : Phase relationships of the CaO–ZnO system in equilibrium with air ( P O 2 = 0.21 atm) have been studied for the first time using the equilibration/quenching/EPMA technique in the temperature range from 1000°C to 1600°C. In this study, the mutual solubility boundaries of the CaO and ZnO phases have been determined. Both CaO and ZnO have obvious solubilities in each other. The maximum solubility of ZnO in solid CaO phase is 23.21 at.% at 1535°C, and ZnO solid phase can take up to 4.81 at.% CaO at 1535°C. The eutectic point and parts of the liquidus lines have also been determined. The eutectic point was found to be at 1535°C ± 2°C and 0.6612 mole fraction of ZnO. No compound was found in this system, and there were two primary phases: halite‐structured CaO (lime) and wurtzite‐structured ZnO (zincite). Results from this study were compared with the CaO–ZnO phase diagram calculated by MTDATA 5.10 and its MTOX 8.1 database. The difference was significant, and the thermodynamic description of the system requires a reassessment.